Effects of Vapor Pressure and Super-Hydrophobic Nanocomposite Coating on Microelectronics Reliability. (September 2015) - Fan, Xuejun; Chen, Liangbiao; Wong, C.P.; Chu, Hsing-Wei; Zhang, G.Q.
ABSTRACT: Modeling vapor pressure is crucial for studying the moisture reliability of microelectronics, as high vapor pressure can cause device failures in environments with high temperature and humidity. To minimize the impact of vapor pressure, a super-hydrophobic (SH) coating can be applied on the exterior surface of devices in order to prevent moisture penetration. The underlying mechanism of SH coating for enhancing device reliability, however, is still not fully understood. In this paper, we present several existing theories for predicting vapor pressure within microelectronic materials. In addition, we discuss the mechanism and effectiveness of SH coating in preventing water vapor from entering a device, based on experimental results. Two theoretical models, a micro-mechanics-based whole-field vapor pressure model and a convection-diffusion model, are described for predicting vapor pressure. Both methods have been successfully used to explain experimental results on uncoated samples. However, when a device was coated with an SH nanocomposite, weight gain was still observed, likely due to vapor penetration through the SH surface. This phenomenon may cast doubt on the effectiveness of SH coatings in microelectronic devices. Based on current theories and the available experimental results, we conclude that it is necessary to develop a new theory to understand how water vapor penetrates through SH coatings and impacts the materials underneath. Such a theory could greatly improve microelectronics reliability.